2016
DOI: 10.11604/pamj.2016.23.221.9372
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of non- neoplastic skin lesions in Ibadan, Nigeria: a histopathologic study

Abstract: Introduction Non-neoplastic skin lesions constitute the majority of skin diseases. There is a paucity of histopathology studies of non-neoplastic skin diseases in Nigeria and the West Africa sub-region in general. This is because the dermato-pathology sub-specialty is poorly developed. Therefore, the main aim of this study is to determine the spectrum of histologically diagnosed non-neoplastic skin lesions in Ibadan, Nigeria. Methods This is a retrospective study. All n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
10
5
1
Order By: Relevance
“…The most common vesicobullous disease is spongiotic dermatitis (84.8%) and this finding is similar to the finding of Ogun GO et al 20 Among papulosquamous diseases, psoriasis and lichen planus are the predominating diseases in many studies. 21,22 In our study, psoriasis and lichen planus are common diseases after erythema dyschromicum perstans.…”
Section: Discussionsupporting
confidence: 88%
“…The most common vesicobullous disease is spongiotic dermatitis (84.8%) and this finding is similar to the finding of Ogun GO et al 20 Among papulosquamous diseases, psoriasis and lichen planus are the predominating diseases in many studies. 21,22 In our study, psoriasis and lichen planus are common diseases after erythema dyschromicum perstans.…”
Section: Discussionsupporting
confidence: 88%
“…In Morocco, a North African country, a large epidemiological study found a mean age of 9.3years [11]. A slight male preponderance found in our study is similar to some previous studies both from our country and elsewhere [4,22,23,30]. Headache was the most common presenting features among supratentorial tumors while unsteadiness of gait occurred more frequently among infratentorial tumors.…”
Section: Discussionsupporting
confidence: 89%
“…The annual incidence appears low; however, it may reflect constraints in accessing care by patients generally and pediatric brain tumor patients specifically. Some of the constraints have been studied extensively [23,30]. At 9.5±2.1 years, the mean age of occurrence of pediatric brain tumors is similar to that from a previous study performed by the lead author of this paper and other researchers from another region of our country [30], as well as a recent retrospective study from a center in our subregion with a smaller sample size [22].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations